Penerapan Metode Single Exponential Smoothing (SES) dalam Peramalan Jumlah Ikan - Nindi Lisnawati; Havid Syafwan; Nurkarim Nehe (Forum Kerjasama Pendidikan Tinggi, 2022)
The fisheries sector is a sector that is one of the factors that can support activities and the Indonesian economy. Fishery resources, especially those in the sea, are natural resources that are freely used by anyone. In carrying out fishing business in Asahan Regency, there has been a cycle of ups and downs from the last ten years, so that the fish supply is not in accordance with its needs. Besides that, it takes a long time to find out the number of fish according to the origin of the catch if there is no technique used. Because this cycle occurs in fish production, it is not yet known how much fish production in the coming year will meet their needs, whether it will increase or decrease, the Government and fishermen in Asahan must be able to take policies to get solutions to these problems. So we need a method to predict the number of fish catches in order to know the predictive value in the next period by using calculations to find the error value for each value using the Single Exponetial Smoothing (SES) method. The results of the study obtained a prediction of the number of fish, namely in the July 2022 period 676836.19 (Kg) with a MAPE value of 3.38%, which value was greater in May 2022 and smaller than June 2022, the Asahan District Fisheries Service must meet the number of fish. in stock of their needs